Lithium supplement agent, positive plate, preparation method of positive plate and lithium ion battery

By covering the surface of the positive electrode lithium supplement material with hydrophobic organics, the problem of unstable positive electrode lithium supplement material in the air is solved, and the energy density and cycle life of lithium-ion batteries are improved.

CN119447520APending Publication Date: 2025-02-14TIANJIN LISHEN BATTERY CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411147446.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-21
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing positive electrode lithium supplement material is unstable in the air, resulting in a decrease in the energy density and cycle life of lithium-ion batteries.

Method used

The hydrophobic protective layer prepared by hydrophobic organic matter RnPOXm or RnSO2Xm is coated on the surface of the positive electrode lithium supplement material to form a self-assembled single molecule layer to improve the air stability of the material.

Benefits of technology

Effectively prevent the surface of the positive electrode lithium supplement material from reacting with water and carbon dioxide in the air, reducing energy density loss, and improving the energy density and cycle stability of lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119447520A_ABST
    Figure CN119447520A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of batteries, and particularly relates to a lithium supplement agent, a positive plate, a preparation method of the positive plate and a lithium ion battery. The lithium supplement agent comprises a positive electrode lithium supplement material and a hydrophobic protection layer coated on the surface of the positive electrode lithium supplement material; the hydrophobic protective layer is prepared from a hydrophobic organic matter RnPOXm or RnSO2Xm, and the hydrophobic organic matter RnPOXm or RnSO2Xm is a hydrophobic organic matter; wherein R is any group; x is one or more of halogen and alkoxy; n and m are natural numbers meeting the valence relationship. According to the lithium supplement agent, on the premise of improving the air stability of the positive electrode lithium supplement material, the energy density loss is reduced to the maximum extent, so that the positive electrode lithium supplement material plays a lithium supplement role at the maximum efficiency, and the energy density and the cycle life of the lithium ion battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of batteries, and in particular relates to a lithium supplement, a positive electrode sheet and a preparation method thereof, and a lithium ion battery. Background Art

[0002] Lithium-ion batteries are a type of energy storage device with excellent performance such as high energy density, excellent cycle stability, environmental friendliness, and rapid charge and discharge. During the first charging process of lithium-ion batteries, a solid electrolyte interface (SE I) film will be formed, which will permanently consume a large amount of active lithium ions from the positive electrode, resulting in a low coulombic efficiency in the first cycle. Graphite materials have an initial irreversible lithium loss of 5%-10%, and Si has an initial irreversible lithium loss of 15%-35%, which reduces the reversible capacity and energy density of lithium-ion batteries. At present, pre-lithiation technology is usually used to supplement lithium to electrode materials to offset the irreversible lithium loss caused by the formation of SE I film, so as to improve the energy density and cycle performance of the battery.

[0003] At present, the pre-lithiation technology mainly includes negative electrode pre-lithiation and positive electrode pre-lithiation. Among them, positive electrode pre-lithiation has high safety, low cost, good compatibility with existing processes, and is more suitable for commercialization. Among them, positive electrode pre-lithiation technology usually uses lithium-rich lithium supplement materials, including Li2NiO2, Li6CoO4, Li5FeO4, Li2Cu 0.8 Ni 0.2 O2, etc. However, lithium-rich lithium-supplementing materials are extremely unstable in the air. Their surfaces will react with carbon dioxide and water in the air to generate Li2CO3 and LiOH (LiOH·H2O), causing serious loss of electrochemical performance.

[0004] In order to improve the air stability of positive electrode lithium supplement materials, the main methods currently used are: ① coating the surface of the positive electrode lithium supplement material with an aluminum oxide coating layer to reduce the amount of residual alkali on the surface of the material and avoid agglomeration in the positive electrode slurry; ② coating the surface of the positive electrode lithium supplement material with a layer of elemental sulfur, which is hydrophobic and can increase the sensitivity of the material to moisture in the air. However, these methods introduce non-negligible additional mass to lithium-ion batteries, which inevitably reduces the energy density of lithium-ion batteries. Summary of the invention

[0005] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a lithium supplement, a positive electrode sheet and a preparation method thereof, and a lithium ion battery.

[0006] To achieve the above object, the technical solution adopted by the present invention is:

[0007] A lithium supplement agent, comprising a positive electrode lithium supplement material and a hydrophobic protective layer coated on the surface of the positive electrode lithium supplement material; the hydrophobic protective layer is composed of a hydrophobic organic substance R n POXm or R n SO2X m Prepared; wherein R is an arbitrary group; X is one or more of halogen, alkoxy, and acyloxy; n and m are natural numbers that satisfy the valence relationship.

[0008] The positive electrode lithium supplement material is Li2N iO2, Li6CoO4, Li5FeO4, Li2Cu 0.8 Ni 0.2 One or more of O2.

[0009] R is one or more of an alkoxy group, a mercapto group, an amino group, an alkenyl group, an amide group, an acyloxy group, an aminopropyl group, a urea group, and an isocyanate group.

[0010] R is an alkoxy group having 1 to 4 carbon atoms, and X is a chloro group, an alkoxy group having 1 to 4 carbon atoms, or an acetoxy group;

[0011] Preferably, R n POX m It is one of CH3O-P(=O)-(OC2H5)2, CH3O-P(=O)-(OC3H7)2, C lP(=O)-(OC4H9)2, H3C-(=O)COP(=O)-(OC4H9)2;

[0012] R n SO2X m For CH3O-(O=)S(=O)-OC2H5, CH3O-(O=)S(=O)-OC4H7,

[0013] One of C l-(O=)S(=O)-OC4H7.

[0014] The present invention also includes a method for preparing the lithium supplement, comprising the following steps: 1) treating a hydrophobic organic substance R n POX m or R n SO2X m and an organic solvent to obtain an organic mixed liquid; 2) adding the organic mixed liquid to the positive electrode lithium replenishing material to react to obtain a solid-liquid mixture; 3) filtering the solid-liquid mixture to obtain a solid powder and drying it to obtain a precursor; 4) heat treating the precursor to obtain a positive electrode lithium replenishing material with a surface modified with a hydrophobic protective layer.

[0015] The mass ratio of the hydrophobic organic matter to the positive electrode lithium supplement material is 1: (0.2-20); preferably 1: (8-9).

[0016] The reaction conditions in step 2) are stirring at 30-80°C for 30-180 min, preferably at 50°C for 45 min.

[0017] The heat treatment conditions in step 4) are: treatment at a temperature of 100 to 300° C. in vacuum or inert atmosphere for 0.5 to 10 h, preferably at 250° C. for 4 h.

[0018] The present invention also includes a positive electrode sheet, including a positive electrode active material, the lithium supplement agent, a conductive agent and a binder;

[0019] The mass ratio of the positive electrode active material, the lithium supplement agent, the conductive agent and the binder is: (90-95): (1-4): (1-3): (1-3); preferably 93.12: 2.88: 2: 2;

[0020] Preferably, the positive electrode active material is LFP;

[0021] Preferably, the conductive agent is a mixture of carbon black and carbon nanotubes, and the ratio of the two is 1:1;

[0022] Preferably, the binder is PVDF.

[0023] The present invention also includes a method for preparing the positive electrode sheet, comprising the following steps: uniformly mixing a positive electrode active material, a lithium supplement agent, a conductive agent, a binder and a solvent to prepare a positive electrode slurry, preferably, the viscosity of the positive electrode slurry is 7000-8000 mPa·s; uniformly coating the positive electrode slurry on a current collector, drying the coating layer, and rolling the coated composite layer electrode to obtain the desired positive electrode sheet.

[0024] The present invention also includes a lithium ion battery, comprising the positive electrode sheet.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] The present invention provides a lithium supplement agent, which can reduce energy density loss to the maximum extent while improving the air stability of positive electrode lithium supplement materials, so that the positive electrode lithium supplement materials can play the lithium supplement role with maximum efficiency, thereby improving the energy density and cycle life of lithium-ion batteries.

[0027] The hydrophobic organic material R used in the hydrophobic protective layer is n POX m or R n SO2X m, it has high reactivity when reacting with -OH on the surface of the positive electrode lithium replenishment material, forming a strong and orderly hydrophobic molecular self-assembled layer on the surface of the positive electrode lithium replenishment material. First, since self-assembly is a thermodynamically spontaneous process, it does not consume energy and usually forms a uniform and complete coating layer; secondly, the monolayer can effectively prevent agglomeration and maintain the uniformity of the nanoscale coating thickness; thirdly, the structure of the self-assembled molecules is diverse and can be customized according to the required performance;

[0028] The self-assembled monolayer on the surface of the positive electrode lithium replenishment material can protect the material surface from erosion by H2O and CO2, and improve the air stability of the positive electrode lithium replenishment material. The self-assembled monolayer is very thin and uniform, forming a dense passivation film on the positive electrode lithium replenishment material, achieving Li without a significant decrease in energy density. + Uniform conduction. During the cycle, the organic matter on the surface of the positive electrode lithium supplement material can effectively prevent the side reaction with the electrolyte, slow down the corrosion of HF in the electrolyte, and improve the cycle stability of the lithium-ion battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is a schematic diagram of the structure of the self-assembled monolayer of the lithium supplement agent of the present invention;

[0030] Figure 2 This is an electron scanning microscope photo of Li5FeO4 of the present invention;

[0031] Figure 3 This is an electron scanning microscope photo of the self-assembled monolayer coated with Li5FeO4 of the present invention;

[0032] Figure 4 This is the X-ray diffraction pattern of the self-assembled monolayer coated with Li5FeO4 of the present invention;

[0033] Figure 5 This is a graph showing the mass change of the self-assembled monolayer coated with Li5FeO4 of the present invention;

[0034] Figure 6 It is a cycle effect diagram of the embodiment of the present invention and the comparative example. DETAILED DESCRIPTION

[0035] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is further described in detail below in conjunction with the accompanying drawings and the best embodiments.

[0036] Example 1

[0037] The hydrophobic organic substance CH3O-P(=O)-(OC2H5)2 was dissolved in ethanol at a volume ratio of 1:5 and stirred for 30 minutes. The positive electrode lithium replenishing material Li5FeO4 was added to the ethanol solution of CH3O-P(=O)-(OC2H5)2 at a mass ratio of 1:8 and magnetically stirred at 50°C for 45 minutes. The solid-liquid mixture was filtered to obtain a solid powder. The powder was heat-treated at 250°C in an argon atmosphere to obtain a positive electrode lithium replenishing material coated with a self-assembled monolayer after 4 hours of treatment.

[0038] Example 2

[0039] The hydrophobic organic substance CH3O-P(=O)-(OC3H7)2 is dissolved in ethanol at a volume ratio of 1:5 and stirred for 30 minutes; the positive electrode lithium replenishing material Li5FeO4 is added to the ethanol solution of CH3O-P(=O)-(OC3H7)2 at a mass ratio of 1:8 and magnetically stirred at 50°C for 45 minutes; the solid-liquid mixture is filtered to obtain a solid powder; the powder is heat-treated at 250°C in an argon atmosphere to obtain a positive electrode lithium replenishing material coated with a self-assembled monolayer after 4 hours of treatment.

[0040] Example 3

[0041] The hydrophobic organic substance CH3O-P(=O)-(OC4H9)2 was dissolved in ethanol at a volume ratio of 1:5 and stirred for 30 minutes; the positive electrode lithium replenishing material Li5FeO4 was added to the ethanol solution of CH3O-P(=O)-(OC4H9)2 at a mass ratio of 1:8 and magnetically stirred at 50°C for 45 minutes; the solid-liquid mixture was filtered to obtain a solid powder; the powder was heat-treated at 250°C in an argon atmosphere to obtain a positive electrode lithium replenishing material coated with a self-assembled monolayer after 4 hours of treatment.

[0042] Example 4

[0043] The hydrophobic organic substance Cl-P(=O)-(OC4H9)2 was dissolved in ethanol at a volume ratio of 1:5 and stirred for 30 minutes; the positive electrode lithium replenishing material Li5FeO4 was added to the ethanol solution of Cl-P(=O)-(OC4H9)2 at a mass ratio of 1:8 and magnetically stirred at 50°C for 45 minutes; the solid-liquid mixture was filtered to obtain a solid powder; the powder was heat-treated at 250°C in an argon atmosphere to obtain a positive electrode lithium replenishing material coated with a self-assembled monolayer after 4 hours of treatment.

[0044] Example 5

[0045] The hydrophobic organic substance H3C-(=O)COP(=O)-(OC4H9)2 was dissolved in ethanol at a volume ratio of 1:5 and stirred for 30 minutes; the positive electrode lithium replenishing material Li5FeO4 was added to the ethanol solution of H3C-(=O)COP(=O)-(OC4H9)2 at a mass ratio of 1:8 and magnetically stirred at 50°C for 45 minutes; the solid-liquid mixture was filtered to obtain a solid powder; the powder was heat-treated at 250°C in an argon atmosphere to obtain a positive electrode lithium replenishing material coated with a self-assembled monolayer after 4 hours of treatment.

[0046] Example 6

[0047] The hydrophobic organic substance CH3O-P(=O)-(OC2H5)2 was dissolved in acetone at a volume ratio of 1:5 and stirred for 30 minutes; the positive electrode lithium replenishing material Li5FeO4 was added to the acetone solution of CH3O-P(=O)-(OC2H5)2 at a mass ratio of 1:8 and magnetically stirred at 50°C for 45 minutes; the solid-liquid mixture was filtered to obtain a solid powder; the powder was heat-treated at 250°C in an argon atmosphere to obtain a positive electrode lithium replenishing material coated with a self-assembled monolayer after 4 hours of treatment.

[0048] Example 7

[0049] The hydrophobic organic substance CH3O-P(=O)-(OC2H5)2 was dissolved in ether at a volume ratio of 1:5 and stirred for 30 minutes; the positive electrode lithium replenishing material Li5FeO4 was added to the ether solution of CH3O-P(=O)-(OC2H5)2 at a mass ratio of 1:8 and magnetically stirred at 50°C for 45 minutes; the solid-liquid mixture was filtered to obtain a solid powder; the powder was heat-treated at 250°C in an argon atmosphere to obtain a positive electrode lithium replenishing material coated with a self-assembled monolayer after 4 hours of treatment.

[0050] Example 8

[0051] The hydrophobic organic substance CH3O-P(=O)-(OC2H5)2 was dissolved in ethanol at a volume ratio of 1:6 and stirred for 30 minutes; the positive electrode lithium replenishing material Li5FeO4 was added to the ethanol solution of CH3O-P(=O)-(OC2H5)2 at a mass ratio of 1:9 and magnetically stirred at 50°C for 45 minutes; the solid-liquid mixture was filtered to obtain a solid powder; the powder was heat-treated at 250°C in an argon atmosphere to obtain a positive electrode lithium replenishing material coated with a self-assembled monolayer after 4 hours of treatment.

[0052] Example 9

[0053] The hydrophobic organic substance CH3O-(O=)S(=O)-OC2H5 is dissolved in ethanol at a volume ratio of 1:5 and stirred for 30 minutes; the positive electrode lithium replenishing material Li5FeO4 is added to the ethanol solution of CH3O-(O=)S(=O)-OC2H5 at a mass ratio of 1:8 and magnetically stirred at 50°C for 45 minutes; the solid-liquid mixture is filtered to obtain a solid powder; the powder is heat-treated at 250°C in an argon atmosphere to obtain a positive electrode lithium replenishing material coated with a self-assembled monolayer after treatment for 4 hours.

[0054] Example 10

[0055] The hydrophobic organic substance CH3O-(O=)S(=O)-OC4H7 is dissolved in ethanol at a volume ratio of 1:5 and stirred for 30 minutes; the positive electrode lithium replenishing material Li5FeO4 is added to the ethanol solution of CH3O-(O=)S(=O)-OC4H7 at a mass ratio of 1:8 and magnetically stirred at 50°C for 45 minutes; the solid-liquid mixture is filtered to obtain a solid powder; the powder is heat-treated at 250°C in an argon atmosphere to obtain a positive electrode lithium replenishing material coated with a self-assembled monolayer after treatment for 4 hours.

[0056] Embodiment 11

[0057] The hydrophobic organic substance C l-(O=)S(=O)-OC4H7 is dissolved in ethanol at a volume ratio of 1:5 and stirred for 30 minutes; the positive electrode lithium replenishing material Li5FeO4 is added to the ethanol solution of C l-(O=)S(=O)-OC4H7 at a mass ratio of 1:8 and magnetically stirred at 50°C for 45 minutes; the solid-liquid mixture is filtered to obtain a solid powder; the powder is heat-treated at 250°C in an argon atmosphere to obtain a positive electrode lithium replenishing material coated with a self-assembled monolayer after treatment for 4 hours.

[0058] Example 12

[0059] The hydrophobic organic substance Cl-(O=)S(=O)-OC4H7 is dissolved in acetone at a volume ratio of 1:5 and stirred for 30 minutes; the positive electrode lithium replenishing material Li2NiO2 is added to the acetone solution of Cl-(O=)S(=O)-OC4H7 at a mass ratio of 1:8 and magnetically stirred at 50°C for 45 minutes; the solid-liquid mixture is filtered to obtain a solid powder; the powder is heat-treated at 250°C in an argon atmosphere to obtain a positive electrode lithium replenishing material coated with a self-assembled monolayer after treatment for 4 hours.

[0060] In order to determine the electrochemical performance of the positive electrode lithium replenishing material coated with the self-assembled monolayer, the positive electrode lithium replenishing material obtained by the above-mentioned synthesis of Examples 1-12 was applied to the battery system. The positive electrode slurry was prepared by uniformly mixing the positive electrode active material LFP: the positive electrode lithium replenishing material Li5FeO4: the conductive agent carbon black (Super-P), carbon nanotubes (CNT) and the binder polyvinylidene fluoride (PVDF) in a mass ratio of 93.12:2.88:1:1:2. The viscosity of the positive electrode slurry was 7000-8000mPa·s; the positive electrode slurry was uniformly coated on the aluminum foil current collector, and the coating layer was dried at a drying temperature of 120°C and a drying time of 3min; the surface density of the electrode piece was 32mg / cm 2 The coated composite layer electrode was rolled. After rolling, the thickness of the composite electrode was 148 μm and the compaction density was 2.4 g / cm 3 ; Get the required electrode.

[0061] A 2430-type battery case was used, with the embodiment pole piece and the comparative example pole piece as the positive electrode, the lithium sheet as the negative electrode, the electrolyte Li PF6 / EC+EMC+DEC (1:1:1, volume ratio), Celgard2325 as the diaphragm, and the stainless steel gasket and spring sheet as the support body. The half-cells corresponding to embodiments 1-12 were assembled in the glove box in sequence. The charge and discharge were performed at 0.1C, the charge cut-off voltage was 4.1V, and the discharge cut-off voltage was 2.5V. The first charge and discharge data of the half-cell were obtained as shown in Table 1.

[0062] Table 1

[0063]

[0064] Comparative Example 1

[0065] The positive electrode slurry is prepared by uniformly mixing the positive electrode active material LFP: the carbon-coated modified positive electrode lithium supplement material Li5FeO4: the conductive agent carbon black (Super-P), carbon nanotubes (CNT) and the binder polyvinylidene fluoride (PVDF) in a mass ratio of 93.12:2.88:1:1:2. The viscosity of the positive electrode slurry is 7000-8000mPa·s; the positive electrode slurry is uniformly coated on the aluminum foil current collector, and the coating layer is dried at a drying temperature of 120°C and a drying time of 3min; the surface density of the electrode sheet is 32mg / cm 2 The coated composite layer electrode was rolled. After rolling, the thickness of the composite electrode was 148 μm and the compaction density was 2.4 g / cm 3 ; Get the required electrode.

[0066] The carbon-coated modified positive lithium supplement material Li5FeO4 is prepared by a liquid phase method using glucose as a carbon source. The preparation is specifically carried out in the following manner: 0.98g Li5FeO4 and 20mg glucose are weighed and added to a 50mL beaker, 20-30mL polyethylene glycol (PEG) is added, and after stirring on a magnetic stirrer for 30min, an ultrasonic rod is placed in the beaker for ultrasonication 3 times (3min each time) to obtain a mixed suspension. The suspension is loaded into a 50mL high-temperature reactor and a liquid phase reaction is carried out at 180°C for 6h; after the liquid phase reaction is completed and the reactor temperature drops to room temperature, the suspension in the reactor is taken out for shear dispersion treatment, with a shear rate of 4000r / min, a shear time of 2min, and a shear number of 2 times; thereafter, the product is centrifuged and collected at 7000r / min, and washed 3 times with anhydrous ethanol; finally, the product is dispersed with 10mL-15mL anhydrous ethanol. The mixture was placed in a watch glass and loaded into a tube furnace, and dried in a nitrogen atmosphere at a drying temperature of 100°C and a drying time of 12 h to obtain a carbon-coated modified positive electrode lithium supplement material Li5FeO4.

[0067] Comparative Example 2

[0068] The positive electrode slurry is prepared by uniformly mixing the positive electrode active material LFP: the unmodified positive electrode lithium supplement material Li5FeO4: the conductive agent carbon black (Super-P), carbon nanotubes (CNT) and the binder polyvinylidene fluoride (PVDF) in a mass ratio of 93.12:2.88:1:1:2. The viscosity of the positive electrode slurry is 7000-8000mPa·s. The positive electrode slurry is uniformly coated on the aluminum foil current collector, and the coating layer is dried at a drying temperature of 120°C and a drying time of 3min. The surface density of the electrode sheet is 32mg / cm 2 The coated composite layer electrode was rolled. After rolling, the thickness of the composite electrode was 148 μm and the compaction density was 2.4 g / cm 3 ; Get the required electrode.

[0069] Comparative Example 3

[0070] The positive electrode slurry is prepared by uniformly mixing the positive electrode active material LFP: the conductive agent carbon black (Super-P), carbon nanotubes (CNT) and the binder polyvinylidene fluoride (PVDF) in a mass ratio of 96:1:1:2. The viscosity of the positive electrode slurry is 7000-8000mPa·s. The positive electrode slurry is uniformly coated on the aluminum foil current collector, and the coating layer is dried at a drying temperature of 120°C and a drying time of 3min. The surface density of the electrode sheet is 32mg / cm 2 The coated composite layer electrode was rolled. After rolling, the thickness of the composite electrode was 148 μm and the compaction density was 2.4 g / cm 3 ; Get the required electrode.

[0071] A 2430-type battery case was used, with the electrode sheet of the embodiment and the electrode sheet of the comparative example as the positive electrode, the lithium sheet as the negative electrode, the electrolyte using Li PF6 / EC+EMC+DEC (1:1:1, volume ratio), Celgard2325 as the diaphragm, and a stainless steel gasket and a spring sheet as the support. The cells were assembled in the glove box in sequence to obtain half-cells of comparative examples 1-3, respectively.

[0072] According to the present invention, the half-cell initial charge and discharge capacity corresponding to the positive electrode lithium replenishing material coated with the self-assembled monolayer is prepared, among which the half-cell charge and discharge capacity corresponding to Example 8 is the highest. The physical properties and electrical properties of the positive electrode lithium replenishing material coated with the self-assembled monolayer prepared in Example 8 are compared.

[0073] After the self-assembled monolayer coated positive electrode lithium replenishing material prepared by the present invention and the unmodified positive electrode lithium replenishing material were placed in air (temperature 26-30° C., humidity 28%-34%) for 48 hours, the particle size and morphology of the positive electrode lithium replenishing material were observed by electron scanning microscopy.

[0074] From the attached Figure 2 and attached Figure 3 It can be found that the Li5FeO4 ( Figure 3 ) and the original material particles Li5FeO4( Figure 2 ) have no obvious difference in size, and the surface of Li5FeO4 coated with the self-assembled monolayer is smooth, indicating that the surface modification technology of the present invention can well maintain the original morphology and structure of the positive electrode material, while the surface of the original material becomes rough.

[0075] The self-assembled monolayer-coated lithium-ion battery cathode lithium replenishing material and the unmodified cathode lithium replenishing material were analyzed by X-ray diffractometer. Figure 4 It can be found that the Li5FeO4 prepared by the present invention does not have Li2CO3, LiOH (LiOH·H2O) or other impurity peaks. This shows that the self-assembled monolayer of the present invention can well protect the surface of Li5FeO4 from being corroded by H2O and CO2, avoid the generation of impurities Li2CO3 and LiOH (LiOH·H2O), and the surface modification technology will not affect the structure of Li5FeO4.

[0076] The surface of the positive electrode lithium supplement material Li5FeO4 will react with carbon dioxide and water in the air to generate byproducts such as Li2CO3 and LiOH (LiOH·H2O). Figure 5It can be seen that the mass changes of lithium-ion battery positive electrode lithium replenishing materials Li5FeO4 coated with self-assembled monolayer, carbon-coated modified Li5FeO4 and unmodified Li5FeO4 gradually increase with the increase of exposure time in air. Among them, the mass change increase trend of lithium-ion battery positive electrode lithium replenishing material Li5FeO4 coated with self-assembled monolayer is the smallest, and its by-products are the least, indicating that the self-assembled monolayer alleviates the corrosion of H2O and CO2 to a certain extent.

[0077] Half-cell test: 0.1C charge and discharge, charge cut-off voltage is 4.1V, discharge cut-off voltage is 2.5V. From the first charge and discharge data of the half-cell in Table 1, it can be found that the first charge and discharge capacity of the self-assembled monolayer coated Li5FeO4 is higher than that of the unmodified Li5FeO4 and the carbon-coated modified Li5FeO4. The referenced benchmark comparative example 3, that is, the battery without adding Li5FeO4, has a first charge and discharge capacity of 160.89 and 156.03 mAh / g, respectively; the battery with unmodified Li5FeO4 added in comparative example 2 has a first charge and discharge capacity of 162.34 and 156.15 mAh / g, respectively; the battery with carbon-coated modified Li5FeO4 added in comparative example 1 has a first charge and discharge capacity of 163.30 and 157.23 mAh / g, respectively; the battery with self-assembled monolayer-coated Li5FeO4 in embodiment 8 has a first charge and discharge capacity of 165.20 and 158.06 mAh / g, respectively; the energy density of the battery without adding Li5FeO4 is increased by 3.1% and 1.8%, respectively; the energy density of the battery with self-assembled monolayer-coated Li5FeO4, carbon-coated modified Li5FeO4, and unmodified Li5FeO4 is increased by 3.1% and 1.8%, respectively. The capacity retention rates of the batteries with i5FeO4 and without added Li i5FeO4 after 1494 cycles were 98.37%, 96.89%, 94.44% and 93.34%, respectively. Figure 6 2 is a diagram showing the cycle effects of the embodiments of the present invention and the comparative example, and Table 3 is the first charge and discharge data of the half-cell.

[0078] Table 2

[0079]

[0080] In summary, the present invention provides a lithium supplement agent, which, on the premise of improving the air stability of the positive electrode lithium supplement material, minimizes the energy density loss, enables the positive electrode lithium supplement material to play the lithium supplement role with maximum efficiency, and improves the energy density and cycle life of the lithium-ion battery.

[0081] The hydrophobic organic material R used to construct the hydrophobic protective layer n POX m or R nSO2X m , it has high reactivity when reacting with -OH on the surface of the positive electrode lithium replenishment material, forming a strong and orderly hydrophobic molecular self-assembled layer on the surface of the positive electrode lithium replenishment material. First, since self-assembly is a thermodynamically spontaneous process, it does not consume energy and usually forms a uniform and complete coating layer; secondly, the monolayer can effectively prevent agglomeration and maintain the uniformity of the nanoscale coating thickness; thirdly, the structure of the self-assembled molecules is diverse and can be customized according to the required performance;

[0082] The self-assembled monolayer on the surface of the positive electrode lithium replenishment material can protect the material surface from erosion by H2O and CO2, and improve the air stability of the positive electrode lithium replenishment material. The self-assembled monolayer is very thin and uniform, forming a dense passivation film on the positive electrode lithium replenishment material, achieving Li without a significant decrease in energy density. + Uniform conduction. During the cycle, the organic matter on the surface of the positive electrode lithium supplement material can effectively prevent the side reaction with the electrolyte, slow down the corrosion of HF in the electrolyte, and improve the cycle stability of the lithium-ion battery.

[0083] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A lithium supplement, characterized in that: It includes a positive electrode lithium replenishing material and a hydrophobic protective layer coated on the surface of the positive electrode lithium replenishing material; the hydrophobic protective layer is composed of a hydrophobic organic substance R n POX m or R n SO2X m Prepared; wherein R is an arbitrary group; X is one or more of halogen, alkoxy, and acyloxy; n and m are natural numbers that satisfy the valence relationship.

2. The lithium supplement according to claim 1, characterized in that: The positive electrode lithium supplement materials are Li2NiO2, Li6CoO4, Li5FeO4, Li2Cu 0.8 Ni 0.2 One or more of O2.

3. The lithium supplement according to claim 1, characterized in that: R is one or more of an alkoxy group, a mercapto group, an amino group, an alkenyl group, an amide group, an acyloxy group, an aminopropyl group, a urea group, and an isocyanate group.

4. The lithium supplement according to claim 1, characterized in that: R is an alkoxy group having 1 to 4 carbon atoms, and X is a chloro group, an alkoxy group having 1 to 4 carbon atoms, or an acetoxy group; Preferably, R n POX m It is one of CH3O-P(=O)-(OC2H5)2, CH3O-P(=O)-(OC3H7)2, Cl-P(=O)-(OC4H9)2, H3C-(=O)COP(=O)-(OC4H9)2; R n SO2X m For CH3O-(O=)S(=O)-OC2H5, CH3O-(O=)S(=O)-OC4H7, One of Cl-(O=)S(=O)-OC4H7.

5. A method for preparing the lithium supplement according to any one of claims 1 to 4, characterized in that: The steps include: 1) adding a hydrophobic organic substance R n POX m or R n SO2X m and an organic solvent to obtain an organic mixed liquid; 2) adding the organic mixed liquid to the positive electrode lithium replenishing material to react to obtain a solid-liquid mixture; 3) filtering the solid-liquid mixture to obtain a solid powder and drying it to obtain a precursor; 4) heat treating the precursor to obtain a positive electrode lithium replenishing material with a surface modified with a hydrophobic protective layer.

6. The preparation method according to claim 5, characterized in that: The mass ratio of the hydrophobic organic matter to the positive electrode lithium supplement material is 1: (0.2-20); preferably 1: (8-9).

7. The preparation method according to claim 5, characterized in that: The reaction conditions in step 2) are stirring at 10-80°C for 30-180 min; preferably at 50°C for 45 min. The heat treatment conditions in step 4) are: treatment at a temperature of 100 to 300° C. in vacuum or inert atmosphere for 0.5 to 10 h; preferably treatment at 250° C. for 4 h.

8. A positive electrode sheet, characterized in that: It comprises a positive electrode active material, a lithium supplement agent according to any one of claims 1 to 4, a conductive agent and a binder; The mass ratio of the positive electrode active material, the lithium supplement agent, the conductive agent and the binder is (90-95): (1-4): (1-3): (1-3); preferably 93.12: 2.88: 2: 2; Preferably, the positive electrode active material is LFP; Preferably, the conductive agent is a mixture of carbon black and carbon nanotubes, and more preferably the ratio of the two is 1:1; Preferably, the binder is PVDF.

9. A method for preparing the positive electrode sheet according to claim 8, characterized in that: The method comprises the following steps: uniformly mixing a positive electrode active material, a lithium supplement agent, a conductive agent, a binder and a solvent to prepare a positive electrode slurry, preferably, the viscosity of the positive electrode slurry is 7000-8000 mPa·s; uniformly coating the positive electrode slurry on a current collector, drying the coating layer, and rolling the coated composite layer electrode to obtain a desired positive electrode sheet.

10. A lithium ion battery, characterized in that: Including the positive electrode sheet as claimed in claim 8.